Apuntes metodológicos para el análisis narrativo de datos visuales en psicología (2012)
This article presents a methodological reflection on the analysis of visual narratives in psychological research. The present study is based on contextual analysis of the audiovisual material produced in a psychoeducational intervention in a school in the metropolitan region of Barcelona, where the collaborative production of films has shown itself as a fundamental tool for the production of a discussion about the identity constructions of the participants as about their schooling too. It is here intended to discuss some methodological aspects of the construction of a benchmark for the analysis of audiovisual material in a dialogical perspective with emphasis on the theoretical framework of Cultural Psychology.